Antibacterial and Antifungal Activity of Medicinal Orchids Growing in Nepal - Marasini, Ramesh; Joshi, Susan (Journal of Nepal Chemical Society, 2013)
Antibacterial activities of different extracts of epiphytic orchids were tested against 5 species of bacteria and antifungal activities were tested against 3 species of fungi. All orchid extracts showed good bacterial Zone of Inhibition (ZOI) against Staphylococcus aureus. The crude extracts of Pholidota imbricata and Coelogyne cristata were shown highest activity against Vibrio cholerae and Staphylococcus aureus respectively. The MIC and MBC value of the extracts of Pholidota imbricata and Coelogyne cristata were found to be 62.5 mg/ml, 31.25 mg/ml and 125 mg/ml, 250 mg/ml against Vibrio cholerae and Staphylococcus aureus respectively. Only Pholidota imbricata and Pholidota articulata extracts were shown fairly good activity but all others extracts were shown very less activity or even failed to show any activity against fungal organisms. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9259 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 104-109 Uploaded date: 12/5/2013